2020
DOI: 10.1007/s11442-020-1743-6
|View full text |Cite
|
Sign up to set email alerts
|

Designing a spatial pattern to rebalance the orientation of development and protection in Wuhan

Abstract: Patterns of spatial development and protection form a basic category of geoscience, and redesigning them is a popular subject of research in regional sustainable development that is important for ecological civilization construction. The authors here report a case study of Wuhan city using the circuit theory model and minimum cumulative resistance (MCR) model to rebalance its spatial protection and development. The results show the following: (1) Using the density of the gross domestic product (GDP), density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Comprehensively considering the land use type, terrain, MNDWI, NDVI, road density, and rail density ( Table A1 ), the MCR model was used to construct the ecological cumulative resistance surface of the study area. The general form of the MCR model is as follows [ 37 ]: where R mc is the minimum cumulative resistance, f min is an unknown negative function, D ij is the spatial distance from the source to landscape unit, R i is the resistance coefficient of the landscape unit to the propagation and diffusion process.…”
Section: Methodsmentioning
confidence: 99%
“…Comprehensively considering the land use type, terrain, MNDWI, NDVI, road density, and rail density ( Table A1 ), the MCR model was used to construct the ecological cumulative resistance surface of the study area. The general form of the MCR model is as follows [ 37 ]: where R mc is the minimum cumulative resistance, f min is an unknown negative function, D ij is the spatial distance from the source to landscape unit, R i is the resistance coefficient of the landscape unit to the propagation and diffusion process.…”
Section: Methodsmentioning
confidence: 99%
“…By the end of 2020, the total population of Wuhan was 12.32 million, of whom 10.39 million were urban residents. Rapid urbanization has led to a large amount of urban land expansion and encroachment on other lands, resulting in strong contradictions between urban growth and natural conservation [38,39]. From 2002 to 2019, the area of urban construction land increased by 98.7%, from 1338.75 km 2 to 2646.26 km 2 .…”
Section: Study Areamentioning
confidence: 99%
“…However, the regional economic development in many countries has clearly demonstrated that there is no synchronous relationship between economic growth and rural poverty reduction. In particular, persistent rural poverty is often found in some areas with high-speed economic growth (Ravallion & Wodon, 1999;Ravallion, 2001;Jin et al, 2020a;Zhou & Xiong, 2017;Shujaat & Usman, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%